Telaah kritis model screening saham syariah menuju pasar tunggal ASEAN - M. Ardiansyah; Ibnu Qizam; Abdul Qoyum (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2016)
Shariah stocks is one of the financial sectors that experienced with most significant growth in recentyears. the most important issue in Shariah stock is Stock screening mechanism. The aim of this study isto examine the screening models of Shariah stocks in ASEAN countries. This study is very crucialespecially in the era of ASEAN economic community (AEC). In addition, this study aims to examinesome of the factors that contribute to the differences in screening models applied in five ASEANcountries. By using descriptive method and literature studies approach, this study found a few things.Firstly, there are various models of Shariah stock screening in Indonesia, Malaysia, Singapore, Thailandand Philippines. In this context, the model screening in ASEAN countries have two tendencies, namely;for the country in the majority of the population is Muslim whereby there are many Sharia expert, thenthey will use the specific screening model and applied only in the country, while for the country that themajority is not Muslim, then they will tend to use models of screening that has been used globally forexample DJIM, FTSE, etc. This second pattern has been applied by Singapore, Thailand and Philippines.Secondly, differences in shariah screening models influenced by several factors, namely; differencesin social structure of a country where the Islamic stock market is located; the difference in the financialindustry that exist in the country will affect on the difference of screening models; and differences sectembraced by most scholars in a country is one of the fundamental factors in determining stock screeningmodel of sharia in 5 ASEAN Countries.